Konseling individu rational emotive behavior: studi eksperimen terhadap peningkatan konsep diri - Dian Setyowati; Suwarjo Suwarjo (Jurnal Konseling dan Pendidikan, 2021)
The study aimed to determine the effectiveness of individual counseling to improve the students’ self-concept with the "Rational Emotive Behavior" technique. This research was single subject experimental design with quantitative study. The population were students in class X in Marketing at SMK N 1 Depok and had a negative self-concept. The purposive sampling were used. Data collection was done used a questionnaire. Data analysis techniques used Wilcoxon test with a significance level of 5%, and the result analysis showed improvement of students’ self concept score. The Wilcoxon test evidenced by the Zcount value of -2.201 and showed the level of significance was less than 0,05 (p = 0.028